High temperature annealing of ion irradiated tungsten. (15th May 2015) - Ferroni, Francesco; Yi, Xiaoou; Arakawa, Kazuto; Fitzgerald, Steven P.; Edmondson, Philip D.; Roberts, Steve G.
Abstract: Transmission electron microscopy of high temperature annealing of pure tungsten irradiated by self-ions was conducted to elucidate microstructural and defect evolution in temperature ranges relevant to fusion reactor applications (500–1200 °C). Bulk isochronal and isothermal annealing of ion irradiated pure tungsten (2 MeV W + ions, 500 °C, 10 14 W + /cm 2 ) with temperatures of 800, 950, 1100 and 1400 °C, from 0.5 to 8 h, was followed by ex situ characterisation of defect size, number density, Burgers vector and nature. Loops with diameters larger than 2–3 nm were considered for detailed analysis, among which all loops had b = 1 2 〈 1 1 1 〉 and were predominantly of interstitial nature. In situ annealing experiments from 300 up to 1200 °C were also carried out, including dynamic temperature ramp-ups. These confirmed an acceleration of loop loss above 900 °C. At different temperatures within this range, dislocations exhibited behaviour such as initial isolated loop hopping followed by large-scale rearrangements into loop chains, coalescence and finally line–loop interactions and widespread absorption by free-surfaces at increasing temperatures. An activation energy for the annealing of dislocation length was derived, finding E a = 1.34 ± 0.2 eV for the 700–1100 °C range.